2013
DOI: 10.1371/journal.pone.0082899
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Laser Adjuvant for Influenza Vaccine

Abstract: Safe and effective immunologic adjuvants are often essential for vaccines. However, the choice of adjuvant for licensed vaccines is limited, especially for those that are administered intradermally. We show that non-tissue damaging, near-infrared (NIR) laser light given in short exposures to small areas of skin, without the use of additional chemical or biological agents, significantly increases immune responses to intradermal influenza vaccination without augmenting IgE. The NIR laser-adjuvanted vaccine confe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(126 citation statements)
references
References 66 publications
9
117
0
Order By: Relevance
“…Furthermore, a 1-min application of the CW-NIR laser augmented antibody response most efficiently to OVA and an influenza vaccine (whole inactivated PR8 virus) with a T H 1-T H 2 balanced T cell response, and conferred protection in a murine influenza lethal challenge model, whereas the 532 nm Q-Nd:YVO 4 induced a T H 1-skewed response with little impact on protection. 51 Importantly, the protective immune responses induced by the CW-NIR were comparable to those induced by a licensed adjuvant and support the view that LVA might have utility in augmenting responses to intradermal vaccines.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…Furthermore, a 1-min application of the CW-NIR laser augmented antibody response most efficiently to OVA and an influenza vaccine (whole inactivated PR8 virus) with a T H 1-T H 2 balanced T cell response, and conferred protection in a murine influenza lethal challenge model, whereas the 532 nm Q-Nd:YVO 4 induced a T H 1-skewed response with little impact on protection. 51 Importantly, the protective immune responses induced by the CW-NIR were comparable to those induced by a licensed adjuvant and support the view that LVA might have utility in augmenting responses to intradermal vaccines.…”
mentioning
confidence: 54%
“…50 The use of non-destructive lasers to alter tissue immune responses in a manner that can enhance systemic vaccine responses, (laser vaccine adjuvants or LVAs), is a novel approach that has just begun to be explored. LVA treatment of the skin is characterized by a combination of relatively low power densities or irradiances (0.7 to 6.0 W/cm 2 ) combined with fairly high total fluences (energy dose supplied per unit area)-typically in the hundreds of Joules/cm 2 -a combination that is unique compared with most other clinical applications of lasers to the skin 35,[51][52][53] (summarized in Fig. 1).…”
Section: Potential Role Of Lasers As Vaccine Adjuvantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, our previous studies showed most currently used or under developed adjuvants, including aluminum hydroxide (Alum), oil-in-water emulsion and toll-like receptor (TLR) agonists, were not suitable for cutaneous vaccination, because these foreign chemicals often induce severe and long lasting local reactions after being injected into the skin. [8][9][10][11] To address this, the concept of using inherent \danger signals" to alert the immune system was proposed. The inspiration came from an old adjuvant, Alum.…”
Section: Laser Induced Micro-sterile In°ammation Array As Vaccine Adjmentioning
confidence: 99%
“…Alternatively, the concept of laser-based vaccine adjuvant has been proposed and studied in recent years. [6][7][8][9] The key advantage of this technology over traditional chemical adjuvants is there would be no any foreign chemicals administered into our body, holding a great promise for future clinical applications. Because the early practice of laser adjuvant has been reviewed elsewhere, [10][11][12] in this, we will focus on the most recent advances in this¯eld.…”
Section: Introductionmentioning
confidence: 99%